Regulation of Neutrophil NADPH Oxidase, NOX2: A Crucial Effector in Neutrophil Phenotype and Function - Paclet, Marie-Hélène; Laurans, Salomé; Dupré-Crochet, Sophie (Frontiers in Cell and Developmental Biology, 2022)
Reactive oxygen species (ROS), produced by the phagocyte NADPH oxidase, NOX2, are involved in many leukocyte functions. An excessive or inappropriate ROS production can lead to oxidative stress and tissue damage. On the other hand, an absence of ROS production due to a lack of a functional NADPH oxidase is associated with recurrent infections as well as inflammation disorders. Thus, it is clear that the enzyme NADPH oxidase must be tightly regulated. The NOX2 complex bears both membrane and cytosolic subunits. The membrane subunits constitute the flavocytochrome b558, consisting of gp91phox (Nox2) and p22phox subunits. The cytosolic subunits form a complex in resting cells and are made of three subunits (p47phox, p40phox, p67phox). Upon leukocyte stimulation, the cytosolic subunits and the small GTPase Rac assemble with the flavocytochrome b558 in order to make a functional complex. Depending on the stimulus, the NADPH oxidase can assemble either at the phagosomal membrane or at the plasma membrane. Many studies have explored NOX2 activation; however, how this activation is sustained and regulated is still not completely clear. Here we review the multiple roles of NOX2 in neutrophil functions, with a focus on description of its components and their assembly mechanisms. We then explain the role of energy metabolism and phosphoinositides in regulating NADPH oxidase activity. In particular, we discuss: (1) the link between metabolic pathways and NOX2 activity regulation through neutrophil activation and the level of released ROS, and (2) the role of membrane phosphoinositides in controlling the duration of NOX2 activity.